2013
DOI: 10.1063/1.4797483
|View full text |Cite
|
Sign up to set email alerts
|

Tungstate sharpening: A versatile method for extending the profile of ultra sharp tungsten probes

Abstract: The benefits of a new electrochemical etching method for the controlled sharpening of sub-micron tungsten probes are demonstrated. The proposed technique only utilizes the insulating effect of the WO₄(2-) by-product which offers more practical ways of controlling the process parameters. The electrosharpening method was fully automated through the analysis of the process current, bulk coulometry, shadowgraphs, and time lapse microscopy. Tip radii smaller than 15 nm were maintained over a wide range of controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…For comparison, Fig. 5(c) and (d) show the STM images of highly oriented pyrolytic graphite (HOPG) in other works also by their electrochemically fabricated tungsten probes, 27,45 demonstrating an imaging resolution of 0.95 A and 2.1 A, respectively. Therefore, it is clearly indicated that the STM images in this work are with higher quality and ner resolution.…”
Section: Practical Application Of Fabricated Tungsten Probesmentioning
confidence: 97%
See 1 more Smart Citation
“…For comparison, Fig. 5(c) and (d) show the STM images of highly oriented pyrolytic graphite (HOPG) in other works also by their electrochemically fabricated tungsten probes, 27,45 demonstrating an imaging resolution of 0.95 A and 2.1 A, respectively. Therefore, it is clearly indicated that the STM images in this work are with higher quality and ner resolution.…”
Section: Practical Application Of Fabricated Tungsten Probesmentioning
confidence: 97%
“…[9][10][11][12][13] Compared to mechanical methods, [14][15][16][17] ame etching 18 and others, 19,20 electrochemical etching of tungsten wire has been extensively adopted due to its convenience, reliability and easy operation. [21][22][23][24] A number of etching strategies and methods, including the drop-off method, 23 liquid membrane etching, 25 two-step etching, 26 inversing etching 27 and post-annealing, 28 have been developed for the fabrication of various probes. Among them, the drop-off method is the most popular one due to its convenient operability and high controllability.…”
Section: Introductionmentioning
confidence: 99%
“…In the experiment, a 200 ml, 2M NaOH solution is used to electrochemically etch a 3N8 purity, 0.020 ′′ diameter, W wire under a 4.0 V AC potential applied between the W wire (primary electrode) and a carbon counter-electrode. 5,6 A specially designed C-flex bobber sheaths the wire, providing insulation from the solution and restricting the reaction to occur at the air-solution-electrode (ASE) interface [see Figs. 1(a) and 1(b)].…”
mentioning
confidence: 99%